2013
DOI: 10.1080/14613808.2013.788143
|View full text |Cite
|
Sign up to set email alerts
|

The role of musical possible selves in supporting subjective well-being in later life

Abstract: There is now an accepted need for initiatives that support older people's well-being.There is increasing evidence that active engagement with music has the potential to contribute to this. This paper explores the relationship between musical possible selves and subjective well-being in later life. The research reported here formed part of a larger project that focused on how active music-making could support positive cognitive, social and emotional outcomes. The research comprised three UK case study sites, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…These factors include gender, age, peer influence, stereotypes, and the presence of role models (Raider-Roth, Albert, Bircann-Barkey, Gidseg & Murray, 2008;Shepard, Nicpon, Haley, Lind & Ming Liu, 2011;Frazier, 2012;Henry, 2013;Miranda, 2013;Way, Hernandez, Rogers & Hughes, 2013). Research confirms the strong relationship between musical skill and identity 4 development during the school years and subsequent reengagement in musical activity during the adult years (Creech, Hallam, Varvarigou, Gaunt, McQueen & Pincas, 2013;Paparo, 2013).Other research has explored how adolescents, and adolescent boys in particular, develop conceptions of their future possible selves. These studies suggest that the development of possible selves is developmental and sequential, with six stages that progress from conception of an envisioned future self to realisation of that future self (see Hock, Deshler & Schumaker, 2006;Freer, 2009b).…”
mentioning
confidence: 75%
“…These factors include gender, age, peer influence, stereotypes, and the presence of role models (Raider-Roth, Albert, Bircann-Barkey, Gidseg & Murray, 2008;Shepard, Nicpon, Haley, Lind & Ming Liu, 2011;Frazier, 2012;Henry, 2013;Miranda, 2013;Way, Hernandez, Rogers & Hughes, 2013). Research confirms the strong relationship between musical skill and identity 4 development during the school years and subsequent reengagement in musical activity during the adult years (Creech, Hallam, Varvarigou, Gaunt, McQueen & Pincas, 2013;Paparo, 2013).Other research has explored how adolescents, and adolescent boys in particular, develop conceptions of their future possible selves. These studies suggest that the development of possible selves is developmental and sequential, with six stages that progress from conception of an envisioned future self to realisation of that future self (see Hock, Deshler & Schumaker, 2006;Freer, 2009b).…”
mentioning
confidence: 75%
“…Indeed, Withnall and Percy (1994) caution that any prescriptive statements about older learners risk underestimating the rich diversity to be found among our older population. However, our research suggests that a critical-geragogy framework may have particular applications in music, providing key messages that support facilitators in developing musical activities that foster the positive benefits of music and learning (Creech, Hallam, McQueen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The first phase of the Music for Life Project had explored the social, emotional, and cognitive benefits of participation in music among older people (Creech, Hallam, Varvarigou et al, 2013;Hallam et al, 2014). In accordance with the general literature concerned with teaching older learners, the Music for Life Project found that facilitators played a key role in fostering effective outcomes for participants.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations